CLASSIFICATION OF SENSITIVE AND LESS SENSITIVE AREAS ALONG THE AEGEAN COASTAL AREAS OF TURKEY - Avaz, Gulsen; Kucuksezgin, Filiz; Tugrul, Suleyman; Tan, Ibrahim; Gunay, Asli Suha; Kuzyaka, Ersan; Özkan, Melek (Parlar Scientific Publications (P S P), 2018)
In the last few decades, due to an enormous increase in urbanization, industrialization and tourism activities, the risk of eutrophication has been gradually gaining more significance, especially for the closed and semi-closed bays in Turkey. In order to protect the marine environment from urbanization and other human activities, decision-makers and organizations involved with environmental management have recognized the necessity for implementation of sound pollution prevention measurement programs and development of realistic investment plans. Correspondingly, in Turkey, the Urban Wastewater Treatment Regulation based on the Urban Wastewater Treatment Directive (91/271/EEC) was put into effect in the beginning of 2006. According to the Directive, classification of aquatic environments with respect to their sensitivity to eutrophication is of crucial importance in planning urban wastewater treatment investments. In this context, the present study aims to, first of all, develop an evaluation methodology for the determination of sensitive/less sensitive areas based on a coastal eutrophication assessment. The methodology takes into account morphological, geographical, hydrodynamic, biochemical and physical/optical characteristics of coastal areas and human activities. By applying this methodology, Izmir Bay and Aliaga Bay were designated as sensitive areas along the Aegean coastal zone of Turkey.
Keywords: Aegean Sea; coastal area; eutrophication; sensitive area; less sensitive area; Urban Wastewater Treatment Directive (UWWTD)